The impact of tourism investment in diversifying sources of income in the Kurdistan Region of Iraq For the years 2003-2018 - Salih, Bahram; Yasin Al-safar, Ahmed (Humanities Journal of University of Zakho, 2021)
The Kurdistan Region of Iraq enjoys a diverse and unique tourism wealth. It is the cradle of humanity and the crossing in which the human race settled from Africa and then traveled to the rest of the world. The presence of many traces of the ancient human presence and the patterns of the first human settlements constitute a factor for almost all types of tourism, but due to the conditions that the region in general and Iraq and the Kurdistan Region in particular, wars and suffering over the past five decades, have limited the government’s tendency to take care of this sector and the revenues have been approved customs, gifts and international aid, and finally, dependence on oil revenues, but despite everything, tourism remained popular during the study period, and the study adopted a positive impact between tourism investment and GDP, and the study concluded that there is a direct relationship between tourism investment and GDP, so a prominent role must be given And the great importance of tourism in generating income through visa facilities and supporting and paying the private sector more. As well as working to link the region with the Arab world with modern and fast transport lines and airspace, opening the largest possible number of air ports and developing the infrastructure in the region.